A protein-conjugate approach to develop a monoclonal antibody-based antigen detection test for the diagnosis of human brucellosis. - Kailash P Patra; Mayuko Saito; Vidya L Atluri; Hortensia G Rolán; Briana Young; Tobias Kerrinnes; Henk Smits; Jessica N Ricaldi; Eduardo Gotuzzo; Robert H Gilman; Renee M Tsolis; Joseph M Vinetz (PLoS Neglected Tropical Diseases, 2014)
Human brucellosis is most commonly diagnosed by serology based on agglutination of fixed Brucella abortus as antigen. Nucleic acid amplification techniques have not proven capable of reproducibly and sensitively demonstrating the presence of Brucella DNA in clinical specimens. We sought to optimize a monoclonal antibody-based assay to detect Brucella melitensis lipopolysaccharide in blood by conjugating B. melitensis LPS to keyhole limpet hemocyanin, an immunogenic protein carrier to maximize IgG affinity of monoclonal antibodies. A panel of specific of monoclonal antibodies was obtained that recognized both B. melitensis and B. abortus lipopolysaccharide epitopes. An antigen capture assay was developed that detected B. melitensis in the blood of experimentally infected mice and, in a pilot study, in naturally infected Peruvian subjects. As a proof of principle, a majority (7/10) of the patients with positive blood cultures had B. melitensis lipopolysaccharide detected in the initial blood specimen obtained. One of 10 patients with relapsed brucellosis and negative blood culture had a positive serum antigen test. No seronegative/blood culture negative patients had a positive serum antigen test. Analysis of the pair of monoclonal antibodies (2D1, 2E8) used in the capture ELISA for potential cross-reactivity in the detection of lipopolysaccharides of E. coli O157:H7 and Yersinia enterocolitica O9 showed specificity for Brucella lipopolysaccharide. This new approach to develop antigen-detection monoclonal antibodies against a T cell-independent polysaccharide antigen based on immunogenic protein conjugation may lead to the production of improved rapid point-of-care-deployable assays for the diagnosis of brucellosis and other infectious diseases.